2016
DOI: 10.1136/gutjnl-2016-311550
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy does not decrease the risk of future colectomy in UC: results from a large cohort and meta-analysis

Abstract: Objectives Early appendectomy is inversely associated with the development of ulcerative colitis (UC). However, the impact of appendectomy on the clinical course of UC is controversial, generally favoring a milder disease course. We aim to describe the effect appendectomy has on the disease course of UC with focus on the timing of appendectomy in relation to UC diagnosis. Design Using the National Institute of Diabetes and Digestive and Kidney Diseases IBD Genetics Consortium database of UC patients, the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 47 publications
3
30
1
3
Order By: Relevance
“…It is concerning that some studies have suggested there may be an increased risk of high‐grade dysplasia and colorectal cancer in patients with ulcerative colitis who have undergone appendicectomy. However, a recent systematic review and meta‐analysis suggested that this may be due to colectomy being postponed owing to the positive effect of appendicectomy on disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is concerning that some studies have suggested there may be an increased risk of high‐grade dysplasia and colorectal cancer in patients with ulcerative colitis who have undergone appendicectomy. However, a recent systematic review and meta‐analysis suggested that this may be due to colectomy being postponed owing to the positive effect of appendicectomy on disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Third, appendix may serve as a reservoir for commensal bacteria and therefore its removal could lead to more dynamic changes in the colonic microbiota. Despite compelling evidence suggesting protective role of appendectomy on development of UC, it remains largely unclear whether appendectomy plays a role in the clinical course of patients with UC or proctitis 21,22 . In our study, we also demonstrated appendectomy was associated with increased risk of extension in patients with ulcerative proctitis.…”
Section: Discussionmentioning
confidence: 99%
“…While genetic factors clearly play an important role in the aetiology of IBD,7–10 they cannot explain the recent rise in disease incidence or the proband concordance rate of 38%–62% in monozygotic twins with CD (even less in UC) 11 12. This has encouraged a search for environmental factors and led to the identification of factors such as smoking, oral contraceptives and appendectomy due to appendicitis (data on appendectomy have however been contradictory)13 as potential risk factors in adulthood IBD while less is known for childhood IBD 14–19…”
Section: Introductionmentioning
confidence: 99%